Middle Leading Practices of Facilitation, Mentoring, and Coaching for Teacher Development: A Focus on Intent and Relationality - Edwards-Groves, Christine; Attard, Catherine; Grootenboer, Peter; Tindall-Ford, Sharon (International Journal of Education Policy and Leadership)

(untitled) (Simon Fraser University, University of Delaware, Phi Delta Kappa International, 2023)
While educational institutions are increasingly acknowledging the importance of middle leaders for improving teaching, there is little research on middle leaders’ specific leading practices compared with, for example, principals. Evidence delineating and describing specific middle leading practice is scant. Drawing on practice theory, this article presents preliminary results from the first phase of a four-year Australian project examining the “flow of influence” of middle leading practices on teacher development. Thematic analysis of interviews reveals the multidimensionality of middle leading, and specifically, ways in which the practices of facilitating, mentoring, and coaching are nuanced and distinctive in their arrangement, intent, and relationality. Results have important implications that cannot be ignored by school leaders and policymakers seeking to improve broader systemic support for building and refining middle leading practices.